International trade in oil: Effects on the balance of payments and exchange rates - Renate Ohr (Intereconomics, 1984)
Oil price increases and the persistent OPEC current account surpluses were considered the main problems of economic development in many industrial and developing countries long after the first oil crisis. Since 1983, however, the OPEC surpluses have been completely absorbed and the official base price of petroleum has fallen for the first time in twenty years, although admittedly in terms of a “strong” dollar. Has the serious damage suffered by oil-importing countries in the two oil shocks been completely neutralised, or are the economies of many countries still strongly influenced by the actions and decisions of the OPEC countries?
Keywords: 330; Monetary Policy